Tubectomy of Pregnant and Non-pregnant Female Balinese Macaques (Macaca Fascicularis) With Post-operative Monitoring - Deleuze, Stefan; Brotcorne, Fany; Polet, Roland; Soma, Gede; Rigaux, Goulven; Giraud, Gwennan; Cloutier, Fanny; Poncin, Pascal; Wandia, Nengah; Huynen, Marie-Claude (Frontiers in Veterinary Science, 2021)
Worldwide, primates and humans increasingly share habitats and often enter in conflict when primates thrive in human-dominated environments, calling for special management measures. Reproductive control is increasingly used to manage population growth but very few monitoring data are available. Therefore, the efficiency and implications of such programs require a careful examination. In the context of a three-year sterilization program in wild female long-tailed macaques in Ubud, Bali, we describe the adjustments brought to an endoscopic tubectomy procedure, a permanent sterilization method. We provide a clinical evaluation of this method, and the postoperative monitoring results of the neutered females after release. 140 females (i.e., 41.9% of the reproductive females of the population in 2019) underwent tubectomy over four successive campaigns carried between 2017 and 2019. As for adjustments, this surgical approach was applicable for pregnant females: 28.6% of the treated females were pregnant at the time of the surgery. The procedure used a single lateral port to reach and cauterize both oviducts in non-pregnant as well as in early to mid-term pregnant females. Pregnant females nearer to term required a second lateral port to access both oviducts masked by the size of the gravid uterus. Moreover, we successfully used bipolar thermocauterization without resection to realize the tubectomy. The average duration of the laparoscopic surgery was 14 min for non-pregnant females and 22 min for pregnant females. Animals were released 3h22 in average following their capture. This short holding time, recommended for free-ranging primates, was made possible by the minimal invasiveness of the sterilization approach. A laparoscopic postoperative evaluation conducted on two patients during the following campaign confirmed that the oviducts were definitely disrupted and no longer potent. Moreover, we did not observe any new pregnancy in sterilized females until three years after surgery. The survival rate of the treated females six months after sterilization was high (96.3%) with no major postoperative complications clinically recorded. Among females that were pregnant during surgery, 81.1% experienced term delivery. This study demonstrates the safety and efficiency of endoscopic tubectomy, even for pregnant females, as a mean of wild macaques’ population control.